Behind the Screen: Gender Differences in the Creator Economy - Francesca Gioia; Leo Morabito (Institute of Labor Economics (IZA), 2025)
The content creator economy has rapidly emerged as a new labor market, enabling ordinary individuals equipped with a smartphone or a video camera to embark on real online careers. We analyze over 18,000 YouTube channels created in Italy between 2006 and 2023 and show that, despite being highly flexible and free of entry barriers, the content creator market has not proven capable of solving traditional gender gaps. Our findings indicate that men seized the opportunities offered by the digital world early on, while women began a significant entry only after 2011, with a peak during the COVID-19 pandemic. The thematic area of the content also varies by gender: women are predominantly active in the Beauty and Food topics, whereas men are more present in Technology and Knowledge. Furthermore, female content creators tend to have a shorter permanence on the platform and, despite producing more videos on average, they receive lower engagement and appreciation from audiences. We suggest several interconnected mechanisms that could possibly explain our findings: gender differences in interest in STEM and ICT fields and entrepreneurial skills; the lack of female role models, particularly in non-stereotypical domains; stereotypes and social norms influencing both content production and audience preferences; and greater female aversion to negative feedback.
Keywords: D9; J01; J16; J2; 330; gender differences; content creator; digital economy